Effect of Freeze Thaw Cycles on Myofibrillar Proteins of Chevon - Katekhaye, Anita; Ambadkar, R. K.; Bokde, P.; Rathod, K. S.; Banerjee , Rituparna (Journal of Meat Science, 2014)
Semitendinosus, Semimembranosus and Biceps femoris muscles from goat carcass were collected aseptically, packed in LDPE bags and chilled for 24hrs. Later, chevon was subjected to frozen storage (-18±2°C). One set of meat samples were frozen and thawed in refrigeration temperature (4±10C),whereas, the second and third sets of samples were frozen and thawed at room temperature (37±20C) and in hot water (40±20C), respectively. The freeze thaw cycles were repeated for 3 times.At every freeze thaw cycle, myofibrillar proteins were isolated and analyzed by SDS PAGE. Current study analysed the detailed pattern of myofibrillar proteins of fresh chevon. Also, from the study, it is evident that low molecular weight bands (Polypeptides) increased with increasing number of freeze thaw cycles that could be indication of proteolysis. Also, hot water and room temperature thawing influenced the proteolysis in 3rd freeze thaw cycle due to sudden exposure to high temperature.
Keywords: Chevon; Freeze thaw cycles; Myofibrillar Protein; Troponin; Actin